جهود الشيخ محمد الخضر حسين في الدعوة والإصلاح - جمال عرقوب (جامعة الوادي Université d'eloud, 2024)
هذا البحث المعنون بـ (جهود الشيخ محمَّد الخضر حسين -- في الدعوة والإصلاح) يتناول الإجابة عن إشكالية رئيسة هي: ما الجهود الدعوية والإصلاحية للشيخ محمد الخضر حسين -رحمه الله-؟ وقد انتظم البحث في مقدِّمَةٍ ضمَّت أهمية الموضوع، وإشكالية البحث، وأسباب اختياره، وأهدافه، ومنهجه، والدراسات السَّابقة، وخطة البحث، وأبرز مصادره. ثم فصولٌ أربعةٌ: الفصل الأول: حياة الشيخ الخضر -- الشخصية والعلمية والعملية، والفصل الثاني: جهود العلامة محمد الخضر حسين -- العلميَّة والتطبيقية المتعلقة بالدعوة والداعية؛ والفصل الثالث: مجالات الدعوة عند العلامة محمد الخضر، والفصل الرابع: مصادر العلَّامة محمد الخضر حسين -- في دعوته إلى الله. وفي الأخير توصَّلت إلى عدَّة نتائج من أبرزها: أنَّ الشيخ محمد الخضر حسين مثَّل بإنتاجه الفكري والثقافي المتنوع مدرسةً متكاملةً، كما أنَّ التَّميُّز والثَّراء العلمي والعملي في حياة الشَّيخ أثَّر تأثيرًا نافعًا مباركًا في تكوينه الفكري، وشخصيته الإصلاحية. ثم إنَّ المراحل التاريخية التي مرَّت بها حياة الشيخ وما شهدته من تحوُّلاتٍ وصراعاتٍ فكريةٍ كان له الأثر البالغ في النضوج الفكري للشيخ، وقوة الشخصية الإصلاحية عنده. كما ظهر جليًّا من خلال البحث الشمولية والوسطية في الفكر الإصلاحي عند الشيخ الخضر --، والواقعية في معالجة القضايا الفكرية والدعوية. ومن التوصيات التي يقدمها الباحث التنبيه لحاجة المكتبة الإسلامية إلى دراسات متوالية متخصصةٍ تُعنى بفكر الشيخ وإرثه الإصلاحي والدعوي -خاصَّةً-، فالوصية بتوجيه العناية لهذا الجانب. ومن ذلك التنويه بالحاجة المعرفية إلى إظهار أوجه التَّميُّز في النضال الدعوي والإصلاحي في فكر الشيخ --، سواء تعلق الأمر بالعمل المؤسسي الجمعوي، أو النشاط الصحفي، أو غير ذلك. بالإضافة إلى توجيه عناية الدعاة إلى الله، والعاملين في سلك الإصلاح الديني والتربوي والاجتماعي إلى الرجوع إلى تراث الشيخ العلمي، والإفادة من تجاريه العلمية والعملية، من أجل استخلاص الدروس. This research entitled (The Efforts of Sheikh Muhammad Al-Khidr Hussein - may God have mercy on him - in Dawah and Reform) deals with the answer to a major problem: What are the advocacy and reform efforts of Sheikh Muhammad Al-Khidr Hussein - may God have mercy on him -? The research was organized in an introduction that included the importance of the topic, the problem of the research, the reasons for its selection, its objectives, methodology, previous studies, the research plan, and its most prominent sources. Then four chapters: Chapter One: The personal, scientific and practical life of Sheikh Al-Khidr - may God have mercy on him, and the second chapter: The scientific and applied efforts of the scholar Muhammad Al-Khidr Hussein - may God have mercy on him - related to the call and the preacher, and the third chapter: The fields of advocacy according to the scholar Muhammad Al-Khidr, and the fourth chapter: The sources of the scholar Muhammad Al-Khidr Hussein in his call to God. In the end, I reached several results, most notably: that Sheikh Muhammad Al-Khidr Hussein, with his diverse intellectual and cultural production, represented an integrated school, and that excellence and scientific and practical richness in the life of the Sheikh had a beneficial and blessed impact on his intellectual formation, and his reformist personality. Moreover, the historical stages that the Sheikh's life went through and the transformations and intellectual conflicts it witnessed had a great impact on the intellectual maturity of the Sheikh, and the strength of his reformist personality. It was also evident through research on comprehensiveness and moderation in the reformist thought of Sheikh al-Khidr (may Allah have mercy on him), and realism in addressing intellectual and advocacy issues. One of the recommendations made by the researcher is to alert the need of the Islamic library to successive specialized studies concerned with the thought of the Sheikh and his legacy of reform and advocacy -in particular- the commandment to direct attention to this aspect. This includes mentioning the cognitive need to show the distinctions in the advocacy and reform struggle in the thought of the Sheikh (may Allah have mercy on him), whether it is related to associative institutional work, journalistic activity, or otherwise. In addition to directing the attention of preachers to God, and those working in the religious, educational and social reform corps to refer to the Sheikh's scientific heritage, and to benefit from his scientific and practical trades, in order to draw lessons.
أطروحة دكتوراه
Keywords: الإصلاح; الدعوة; الخضر حسين; الجهود